Serum IgG as a Marker for Opisthorchis viverrini-Associated Cholangiocarcinoma Correlated with HER2 Overexpression - Titapun, Attapol (Int J Gen Med, 2020)
BACKGROUND: Serum antibody for Opisthorchis viverrini (OV) is strong evidence for a history of OV infection in people. Currently, no studies have examined whether varying cholangiocarcinoma (CCA) prevalence levels are linked to previous OV infection nor have they provided comprehensive assessment and characterization of OV-associated CCA. OBJECTIVE: Our study examined the prevalence of serum IgG antibodies for OV-positive CCA cases and determined whether there were correlations of IgG antibodies with histopathologic features, HER2, PD-L1, and FGFR2 expression, as well as their roles on the patients’ survival. METHODS: The study involved 221 CCA surgical patients at Khon Kaen University Hospital, Thailand, from 2005 to 2017. Serum specimens were tested for OV IgG by ELISA. CCA tissue microarrays were used to examined for HER2, PD-L1, and FGFR2 expression. Logistic regression was used to investigate an association between factors and IgG. Cox regression was used to determine factors that affected CCA patient survival. RESULTS: IgG for OV were positive in 162 cases, and the prevalence was 73.3% (95% CI=68.0–78.7). About three quarters (78.3%) had large duct type tumors and concomitant intraductal papillary neoplasm of bile ducts (IPNB) occurred in 92 (50%) cases. HER2 expression was positive in 94 (61.4%) cases. Positive PD-L1 and FGFR2 expression occurred in 125 (83.9%) and 100 (67.1%) cases. IgG for OV had no significant correlation to any histological feature but had significant correlation with HER2 overexpression with adjusted OR=2.32 (95% CI=1.09–4.96, P=0.03). Cases of CCA with OV IgG positive had a significantly poor prognosis with adjusted HR=1.66 (95% CI=1.13–2.43, P=0.01). CONCLUSION: We found a high prevalence of serum IgG for OV-positive CCA patients and a correlation with overexpression of HER2. Moreover, IgG for OV and HER2 expression indicated poor survival of CCA. Therefore, future clinical studies for anti-HER2 treatments should focus on OV-associated CCA.